(Chitosan-Iodine) Bio-Films and Its Applications - Abdul Rida, Duaa; Kareem Ahmed, Jaleel; Jabbar Braihi, Auda (International Journal of Psychosocial Rehabilitation, 2020)
Films manufactured from chitosan polymer and iodine (I2) for treating wounds, infected, and burned areas. Chitosan-iodine composites are prepared by adding 14 wt.% iodine element to the chitosan matrix. As a solution and film (coating and composite) states are used to investigate their healing actions. Evaluating healing action is done by applying these solutions and films to the injured rabbits and comparing them with the flamazine cream treatment medical ointment. The antibacterial activity was checked in Hilla General Teaching Hospital by exposing the prepared samples to the action of Staphylococcus aureus (gram-positive), Escherichia coli (gram-negative), and Pseudomonas aeruginosa (gram-negative) microorganisms. The agar-well diffusion method was used to evaluate the antibacterial action by measuring the inhibition zone area. Results showed that the prepared composite film is the best, having diameter zones 45, 35, and 15 mm of antibacterial ability against Staphylococcus aureus, Escherichia coli, and Pseudomonas microorganisms, respectively. Density and wettability of chitosan film increased with the addition of I2, and the wettability of composite film as a function of time is greater than that of the pure and coating films. Also, the weight loss results proved that the losses of iodine in coated film (5.4%) are higher than in composite film (2.6%). Glass transition temperature (Tg) results proved the presence of physical interactions between chitosan and I2. The calculations of Tg values show that iodine gives energy to the chitosan film, to the composite film (11.69 kJ mol-1) and to the coated film (0.95 kJ mol-1). Complete healing of wound rabbits is obtained within seven days compared with the negative control (without treatment). Both types of films (coating and composite) show good healing power compared with present medical ointment, but composite film was better. The test is carried on to show the limited ability for area healing power of chitosan, iodine, chitosan-I2-coated, and composite films. Also, tests are carried out to join the films with the affected area, i.e., to create a new skin.